Acupuncture trials and informed consent - Miller, F G (BMJ Group, 2007)
Participants are often not informed by investigators who conduct randomised, placebo‐controlled acupuncture trials that they may receive a sham acupuncture intervention. Instead, they are told that one or more forms of acupuncture are being compared in the study. This deceptive disclosure practice lacks a compelling methodological rationale and violates the ethical requirement to obtain informed consent. Participants in placebo‐controlled acupuncture trials should be provided an accurate disclosure regarding the use of sham acupuncture, consistent with the practice of placebo‐controlled drug trials.